2023
DOI: 10.1017/s0373463322000595
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity risk assessment of VDR

Abstract: The voyage data recorder (VDR) is a data recording system that aims to provide all navigational, positional, communicational, sensor, control and command information for data-driven investigation of accidents onboard ships. Due to the increasing dependence on interconnected networks, cybersecurity threats are one of the most severe issues and critical problems when it comes to safeguarding sensitive information and assets. Cybersecurity issues are extremely important for the VDR, considering that modern VDRs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Yoo et al [81] focused on AI technology's cybersecurity implications in the context of autonomous ships, applying the SQUARE methodology to identify vulnerabilities and envisage cyberattack scenarios. In a similar vein, Söner et al [82] delved into the variety of challenges that come with securing the maritime environment. Söner et al identified cybersecurity concerns for voyage data recorders (VDRs) on ships, which are crucial for accident investigation.…”
Section: Data Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yoo et al [81] focused on AI technology's cybersecurity implications in the context of autonomous ships, applying the SQUARE methodology to identify vulnerabilities and envisage cyberattack scenarios. In a similar vein, Söner et al [82] delved into the variety of challenges that come with securing the maritime environment. Söner et al identified cybersecurity concerns for voyage data recorders (VDRs) on ships, which are crucial for accident investigation.…”
Section: Data Securitymentioning
confidence: 99%
“…There is a consensus on the need for comprehensive education and training programs to build sufficient cybersecurity knowledge across all levels of the industry. • Data Security: Data security has been identified as a critical area of advancement, with the research proposing various strategies to protect data within the maritime sector[60,[81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. This includes the development of technologies and processes to ensure the integrity and confidentiality of maritime data.…”
mentioning
confidence: 99%
“…Ships and ports are the central roles of maritime transportation with several shipboard navigation systems, such as ECDIS and AIS, as well as Voyage Data Recorder (VDR), providing real-time sailing information to ensure safety and efficiency (Söner et al, 2023). Meanwhile, the number of ship-and portinvolved cyber-attacks (Silverajan et al, 2018) has increased, using such instruments as code injection, tampering and modification, GPS and AIS spoofing, signal jamming and information eavesdropping, as well as link disruption, which can utilise one or several vectors, such as a positioning system, firmware, sensors, VDRs, intra-vessel networks, vessel-to-shore communications, remote operation systems and so on.…”
Section: Recognising Maritime Cyber-threatsmentioning
confidence: 99%
“…Breaches in system security can compromise the control, navigation, or communication of autonomous ships, leading to accidents or malicious activities [14,15]. Autonomous systems involve the integration of multiple components, including software, hardware, sensors, and communication systems [16].…”
Section: Introductionmentioning
confidence: 99%